Diversity Of Fusarium Species Associated With Bakanae Disease Of Rice In Malaysia And Indonesia - Zainudin, Nur Ain Izzati Mohd (2007)
Many diseases were reported to be associated with rice; one of the diseases is bakanae that caused by Fusarium spp .. The main objective of these studies was to characterize Fusarium spp. in Section Liseola isolated from bakanae-infected rice in Malaysia and Indonesia by using several approaches in order to determine the similarities and variabilities between the species. Results during sampling bkanae disease were widespread in Peninsular Malaysia and three provinces in Indonesia (East Java, Padang and Samarinda) except in Yan, Kedah. The typical symptoms of bakanae disease were abnormal elongation, yellowish leaves, produced a few tillers and wiry adventitious roots. Some infected plants were stunted and those survived appeared normal until maturity but produced empty and discoloured grains. A total of 212 strains of Fusarium were isolated from bakanae-infected rice plants and they were initially identified using morphological characteristics for species delimitation. The highest number (127) of Fusarium strains were classified into five species in Section Liseola Le. F. fujikuroi (most frequently, 37.3%), F. verticiflioides, F. proliferatum, F. sacchari and F. subgJutinans.. Other species were also isolated such as F. semitectum, F. oxysporum, F. solani, F. longipes, F. chlamydosporum and F. equiseti. Pathogenicity test showed F. fujikuroi was confirmed as the pathogen of bakanae disease on rice in Malaysia and Indonesia with varying levels of virulence.